A critical review of the application of environmental scenario exercises. (October 2015) - Wodak, Josh; Neale, Timothy
Highlights: Critical review of types of environmental scenario and their applications. Review of practical issues of scenario exercise usage. Review of measures of success in scenario exercises. Abstract: Scenario exercises have become instrumental across multiple fields, from their original usage in business and military planning, to being ubiquitous in environmental planning and policy formation. This article critically reviews whether there are explicit and imminent divisions between how scenario exercises are used and discussed, with particular focus on the literature of qualitative scenarios concerning environmental challenges. The authors interrogate what scenario exercises are in actual practice, in the context of what they are used for and how they are designed, before then considering the criteria for determining 'success' for a scenario exercise. The particular focus of the literature analysed is in the emergence of the discipline of 'environmental scenarios', being scenarios concerned with 21st Century environmental challenges such as the influence of climate change on the notion of natural hazards.